L. D. (Buck) Wood and Bob Marlow standing in front of the streetcar. - (:unkn) unknown (Forsyth County Public Library, 2009)
Date of the photo is undetermined.
L. D. (Buck) Wood and Bob Marlow standing in front of the streetcar.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth